The influence of teacher discourse moves on comprehensibility of language content by English first additional language (EFAL) learners - Masube, Elizabeth Tobani (University of Limpopo (Turfloop Campus), 2010)
This study was intended to investigate how teacher discourse moves influence comprehensibility of language content by the English First Additional Language (EFAL) learner and promote active participation by the learner in classroom interaction. The research is a Case Study which was conducted at a primary school in the Greater Sekhukhune District in Limpopo Province The Qualitative research approach was applied in the Case Study since the research is concerned with experience as it is lived ‘or felt’ or ‘undergone’ by participants. the key concern of this research is understanding the phenomenon of interest, from the participants’ perspectives, not the researcher’s. The situation in most Black schools is that first of all, teachers who teach English First Additional Language (EFAL) are not first speakers of English themselves. Secondly, learners have a problem of acquiring information through English as an additional language hence the question of comprehensibility of English language content. Teachers and especially learners are de-motivated as they lose interest in what goes on in Englishclassroom interaction due to the comprehensibility of English First Additional Language content As participant observer the researcher in this study concludes that the use of discourse moves by the teacher in classroom interaction enables the learner to comprehend the language content. Also that the teacher’s code-switching and code-mixing into the learners’ home language develops not only comprehensibility of EFAL language content but most of all promotes active learner participation in classroom interaction. This in turn helps the teacher to achieve the desired learning outcomes.
Thesis (M.ED.) --University of Limpopo, 2010
Keywords: English language teaching; 372.6521; English language -- Study and teaching -- Foreign speakers